2013
DOI: 10.1371/journal.pone.0074102
|View full text |Cite
|
Sign up to set email alerts
|

TOX3 Mutations in Breast Cancer

Abstract: TOX3 maps to 16q12, a region commonly lost in breast cancers and recently implicated in the risk of developing breast cancer. However, not much is known of the role of TOX3 itself in breast cancer biology. This is the first study to determine the importance of TOX3 mutations in breast cancers. We screened TOX3 for mutations in 133 breast tumours and identified four mutations (three missense, one in-frame deletion of 30 base pairs) in six primary tumours, corresponding to an overall mutation frequency of 4.5%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
1
17
0
2
Order By: Relevance
“…TOX3 is involved in bending and unwinding of DNA and alteration of chromatin structure 28 . It is a known risk gene for breast cancer 29 , where it is also somatically mutated at a moderate rate 30 . In line with this, we observed the most SNVs in breast cancer (n=5).…”
mentioning
confidence: 99%
“…TOX3 is involved in bending and unwinding of DNA and alteration of chromatin structure 28 . It is a known risk gene for breast cancer 29 , where it is also somatically mutated at a moderate rate 30 . In line with this, we observed the most SNVs in breast cancer (n=5).…”
mentioning
confidence: 99%
“…BRCA1 and BRCA2 genes encode tumor suppressing proteins, and it has been shown that a mutation in these genes increases susceptibility to breast cancer [21], [22]. FGFR2 and TOX3 mutations have both been linked to an increase in breast cancer risk though their molecular mechanisms are not well understood [23], [24]. Finally, TP53 is an important gene in many cancers, and it has been shown that a change in the p53 pathway leads to more aggressive breast cancer.…”
Section: Experimental Evaluationmentioning
confidence: 99%
“…Multiple studies have demonstrated that the overregulation of TOX is associated with tumor progression [21]. Deregulation of TOX expression in cancer can be roughly attributed to two mechanisms: genetic alteration [22,23] and epigenetic events [24].…”
Section: Introductionmentioning
confidence: 99%